2022
DOI: 10.55446/ije.2021.252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Protectants Against Pulse Beetle Callosobruchus chinensis Infesting Mungbean

Abstract: Efficacy of some seed protectants against pulse beetle Callosobruchus chinensis (L.) in stored mungbean variety MH 421 was evaluated under laboratory conditions in the Department of Entomology, CCSHAU, Hisar during October-December 2018. The result revealed that the neem leaf powder (30g/ kg) and neem oil (10 ml/ kg) were found most effective with maximum adult mortality (100 and 98.33%, respectively), lowest grain damage and weight loss (1.06 and 1.20%) and (0.75 and 0.81%, respectively), followed by mentha o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…The results in respect of use of neem oil as seed protectant corroborated with those of [30] who observed no seed damage by C. chinensis in seeds of horse gram when treated with neem oil at 5 ml/kg seed. Pigeon pea seeds coated with neem and castor oil gave significant protection against pulse beetle compared to the untreated control [31] also supports the present findings [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…The results in respect of use of neem oil as seed protectant corroborated with those of [30] who observed no seed damage by C. chinensis in seeds of horse gram when treated with neem oil at 5 ml/kg seed. Pigeon pea seeds coated with neem and castor oil gave significant protection against pulse beetle compared to the untreated control [31] also supports the present findings [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…Eggs were occasionally found scattered, even on container edges. Fecundity ranged from 84 to 93 eggs per female, with an average of 88.80±4.08 eggs which is in accordance with the findings of Kumari et al (2020) found fecundity in the range of 71-87 with a mean of 78.93±4.83. The highest number of eggs was laid on the second day after adult release, with the first day following closely.…”
Section: Fecunditysupporting
confidence: 90%
“…Jaiswal et al (2018 and2019) reported around 60% loss in weight of the pulses due to pulse beetle. Till date the biology of C. chinensis has been explored on chick pea (Chandel and Bhaudaria, 2015;Rana et al, 2020), green gram (Devi and Devi, 2014;Kumari et al, 2020;Gopi and Singh 2020), black gram (Dalal et al, 2020), cowpea (Augustine and Balikai, 2018), moth bean (Meghwal and Singh 2005) and multiple hosts (Patel et al, 2005;Hosamani et al, 2018;Jaiswal et al, 2018Jaiswal et al, & 2019Mehta and Negi, 2020). Due to differences in the physical characteristics of the host, the type of host has a considerable impact on the insect's development.…”
mentioning
confidence: 99%